Business cycle synchronization: Is it affected by inflation targeting credibility? - Carlos Leandro Delgado-Fuentealba; Iván Araya; Gabriel Pino (SERIEs - Journal of the Spanish Economic Association, 2020)
We empirically study the impact of inflation targeting credibility on business cycle synchronization with G-7 economies. To do this, we use a sample of 15 inflation targeting countries to develop and calculate a reputation-based credibility measure for long- and short-term memory. By using dynamic multipliers through a panel vector autoregressive model, our main findings indicate that greater credibility allows for greater anchoring of inflation expectations by economic agents. This would lead to a greater effectiveness of monetary policy in stabilizing the evolution of prices, allowing the output gap to be more sensitive to external aggregate demand shocks. Therefore, countries with inflation targeting regimes must develop and maintain credibility for their monetary policy if they want to encourage greater interactions with the rest of the world.
Keywords: F42; E52; 330; Business cycle synchronization; Credibility; Globalization; Inflation targeting; Panel VAR